Pomen vrtičkarske dejavnosti v Ljubljani za posameznika, okolje in mesto - Bukvič, Karmen (Urbani izziv, 2010)
This article examines the importance of Ljubljana''s plot gardening in relationto three aspects: social, ecological and spatial. Plot gardening in a city, as a common urban practice, is comprised of several aspects, not only food supply, as is stressed in this text. As an informal social activity, it satisfies many individual needs and is related to the quality of life and living environment. It is also important when considering spatial values and preferences because in the process of studying plot gardening as a social phenomenon the cultural specifics and social importance of this activity for Ljubljana residents is being identified. Thus, with favourable conditions and management as well as monitoring of the activity, plot gardening is positive in numerous regards, not only for the plot users but also for the city and the environment as well because the green city system and a positive city imageare important. Disagreements that arose due to issues of cleaning up plotgardens in Ljubljana required a suitable solution to the problems of plot gardening. Considering the facts and in order to prevent the problems that canarise from this activity, the importance of and justification for plot gardening is stressed, particularly concentrating on the advantages of the practice.
Keywords: Ljubljana; urbana sociologija; vrtovi; zelene površine